Fungal Planet description sheets: 14361477 - Y.P. Tan; S.L. Bishop-Hurley; R.G. Shivas; D.A. Cowan; G. Maggs-Klling; S.S.N. Maharachchikumbura; U. Pinruan; K.L. Bransgrove; S. De la Pea-Lastra; E. Larsson; T. Lebel; S. Mahadevakumar; et al. (My University, 2022)
Novel species of fungi described in this study include those from various countries as follows: Argentina , Colletotrichum araujiae on leaves, stems and fruits of Araujia hortorum . Australia , Agaricus pateritonsus on soil, Curvularia fraserae on dying leaf of Bothriochloa insculpta , Curvularia millisiae from yellowing leaf tips of Cyperus aromaticus , Marasmius brunneolorobustus on well-rotted wood, Nigrospora cooperae from necrotic leaf of Heteropogon contortus , Penicillium tealii from the body of a dead spider, Pseudocercospora robertsiorum from leaf spots of Senna tora , Talaromyces atkinsoniae from gills of Marasmius crinis-equi and Zasmidium pearceae from leaf spots of Smilax glyciphylla . Brazil , Preussia bezerrensis fromair. Chile , Paraconiothyrium kelleni from the rhizosphere of Fragaria chiloensis subsp. chiloensis f. chiloensis . Finland , Inocybe udicola onsoilinmixedforest with Betula pendula , Populus tremula , Picea abies and Alnus incana . France , Myrmecridium normannianum on dead culm of unidentified Poaceae . Germany , Vexillomyces fraxinicola from symptomless stem wood of Fraxinus excelsior . India , Diaporthe limoniae on infected fruit of Limonia acidissima , Didymella naikii on leaves of Cajanus cajan , and Fulvifomes mangroviensis on basal trunk of Aegiceras corniculatum . Indonesia , Penicillium ezekielii from Zea mays kernels. Namibia , Neocamarosporium calicoremae and Neocladosporium calicoremae on stems of Calicorema capitata , and Pleiochaeta adenolobi on symptomatic leaves of Adenolobus pechuelii . Netherlands , Chalara pteridii on stems of Pteridium aquilinum , Neomackenziella juncicola (incl. Neomackenziella gen. nov.)and Sporidesmiella junci from dead culms of Juncus effusus . Pakistan , Inocybe longistipitata on soil in a Quercus forest. Poland , Phytophthora viadrina from rhizosphere soil of Quercus robur , and Septoria krystynae on leaf spots of Viscum album . Portugal (Azores) , Acrogenospora stellata on dead wood or bark. South Africa , Phyllactinia greyiae on leaves of Greyia sutherlandii and Punctelia anae on bark of Vachellia karroo . Spain , Anteaglonium lusitanicum on decaying wood of Prunus lusitanica subsp . lusitanica , Hawksworthiomyces riparius from fluvial sediments, Lophiostoma carabassense endophytic in roots of Limbarda crithmoides , and Tuber mohedanoi from calcareussoils. Spain (Canary Islands) , Mycena laurisilvae on stumps and woody debris. Sweden , Elaphomyces geminus from soil under Quercus robur . Thailand , Lactifluus chiangraiensis on soil under Pinus merkusii , Lactifluus nakhonphanomensis and Xerocomus sisongkhramensis on soil under Dipterocarpus trees. Ukraine , Valsonectria robiniae on dead twigs of Robinia hispida . USA , Spiralomyces americanus (incl. Spiralomyces gen. nov.) from office air. Morphological and culture characteristics are supported by DNA barcodes.
Keywords: Plant Pathogens and Fungal Diseases